INTEGRATING AI INTO FINANCIAL CRM A PATH TO PERSONALIZED CUSTOMER ENGAGEMENT - Pradeep Kumar Choudhary, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
AI-Enabled Customer Relationship Management (CRM) has emerged as a transformative approach for financial institutions to enhance customer engagement, improve service delivery, and drive business growth. This paper presents a case study approach to explore the implementation and impact of AI-enabled CRM in the financial industry. Through a comprehensive analysis of real-world examples, we examine how AI technologies, such as machine learning, natural language processing, and predictive analytics, are utilized to personalize customer interactions, anticipate customer needs, and optimize marketing strategies. The case studies highlight the effectiveness of AI-enabled CRM in improving customer satisfaction, increasing cross-selling opportunities, and fostering long-term customer loyalty. Additionally, we discuss the challenges and opportunities associated with implementing AI-driven CRM solutions, along with best practices for maximizing their benefits in the financial sector. Overall, this paper provides valuable insights into the role of AI in revolutionizing customer relationship management practices in the financial industry.